Mitophagy deficiency activates stimulator of interferon genes activation and aggravates pathogenetic cardiac remodeling - Zhou, Guoxiang; Wang, Xiaowen; Guo, Mingyu; Qu, Can; Gao, Lei; Yu, Jiang; Li, Yuanjing; Luo, Suxin; Shi, Qiong; Guo, Yongzheng (Genes & diseases, 2024)
Stimulator of interferon genes (STING) has recently been found to play a crucial role in cardiac sterile inflammation and dysfunction. The role of stimulator of interferon genes (STING) in cardiac sterile inflammation and dysfunction has been recently discovered. This study aims to examine the involvement of STING in pathological cardiac remodeling and the mechanisms that govern the activation of the STING pathway. To investigate this, transverse aortic constriction (TAC) was performed on STING knockout mice to induce pressure overload-induced cardiac remodeling. Subsequently, cardiac function, remodeling, and inflammation levels were evaluated. The STING pathway was found to be activated in the pressure overload-stressed heart and angiotensin II (Ang II)-stimulated cardiac fibroblasts. Loss of STING expression led to a significant reduction in inflammatory responses, mitochondrial fragmentation, and oxidative stress in the heart, resulting in attenuated cardiac remodeling and dysfunction. Furthermore, the exacerbation of pressure overload-induced STING-mediated inflammation and pathological cardiac remodeling was observed when mitophagy was suppressed through the silencing of Parkin, an E3 ubiquitin ligase. Taken together, these findings indicate that STING represents a newly identified and significant molecule implicated in the process of pathological cardiac remodeling and that mitophagy is an upstream mechanism that regulates STING activation. Targeting STING may therefore provide a novel therapeutic strategy for pathological cardiac remodeling and heart failure.